Primary Splenic Angiosarcoma with Liver Metastasis: A Rare Neoplasm Diagnosed on Fine-needle Aspiration Cytology and Cell Block Immunocytochemistry - Sharma, Saniya (J Cytol, 2018)
Primary splenic angiosarcoma is a rare malignant vascular neoplasm of mesenchymal origin. The tumor is highly aggressive and has a high metastatic potential. It is usually diagnosed on histopathological examination of splenectomy specimen. Only few cases of angiosarcoma diagnosed by fine-needle aspiration (FNA) cytology alone have been reported in the literature. The cytologic features of angiosarcoma are heterogeneous, however, diagnosis can be suggested by FNA when vasoformative features are present. A 55-year-old female presented with abdominal pain and hepatosplenomegaly. Computed tomography scan revealed a heterogeneous splenic lesion with liver metastases. FNA from the splenic and liver lesions showed moderately pleomorphic tumor cells closely associated with anastomosing vascular channels. Cell block immunocytochemistry (ICC) showed tumor cells positive for CD31, CD34, CD68 as well as for CD99. FNA supplemented by cell block ICC can render a definite diagnosis of primary splenic angiosarcoma with liver metastasis.